2016
DOI: 10.1080/20477724.2016.1184864
|View full text |Cite|
|
Sign up to set email alerts
|

The molecular and clinical features of dengue during outbreak in Jambi, Indonesia in 2015

Abstract: Dengue is hyperendemic in Indonesia. In 2015, reported cases of dengue fever doubled those of 2014 in the Jambi municipality of Sumatra. We examined viral aetiology and its relationship with disease outcome in Jambi. Dengue-suspected patients' sera were collected and NS1 detection and IgM/IgG serology were performed. Dengue virus (DENV) serotyping was performed using real-time RT-PCR. Envelope genes were sequenced to determine the genotypes of DENV. Clinical, haematologic, and demographic data were recorded. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 26 publications
(24 reference statements)
1
51
1
4
Order By: Relevance
“…A full assessment of the 120 references resulted in the exclusion of 53 references due to the following: full texts were unavailable, and the available abstracts did not include adequate information to satisfy our outcome, the full text did not include adequate or complete serotype data, and nonstandard methods were used for serotyping. This resulted in 67 eligible studies, of which 13 references were from national journals . An additional 11 studies were included from reference list .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A full assessment of the 120 references resulted in the exclusion of 53 references due to the following: full texts were unavailable, and the available abstracts did not include adequate information to satisfy our outcome, the full text did not include adequate or complete serotype data, and nonstandard methods were used for serotyping. This resulted in 67 eligible studies, of which 13 references were from national journals . An additional 11 studies were included from reference list .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 78 eligible studies were included for DENV serotype analysis . Of all the eligible studies, four studies were conducted based on mosquito isolates while the remaining studies assessed DENV isolates from human samples . Sixty two studies investigated dengue cases among local inhabitants of Indonesia,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For Indonesia, the government reported 112,511 DF cases and 871 fatalities in 2013 (29). In 2015, the reported cases of dengue fever doubled those of 2014 in the Jambi, Indonesia (30). A recent study reported that the DHF incidence increased rapidly but the case fatality ratio of DHF decreased considerably in recent decades (31).…”
Section: Global Prevalencementioning
confidence: 99%